Passiflora franciscoi, a new species of Passiflora subgenus Astrophea (Passifloraceae) from Colombia - Aguirre-Morales, Adriana Carolina; Bonilla-Morales, Miguel Macgayver; Caetano, Creucí Maria (Phytotaxa, 2016)
A new species of Passiflora subgenus Astrophea from the Colombian Orinoquia is described, illustrated, and placed in the supersection Pseudoastrophea section Pseudoastrophea. Passiflora franciscoi, a woody liana with tendrils, is recognized by its white flower, orange corona covered with red spots and a short and dark red appendix in the center of the filaments, its leaf blade emarginate at apex and cordate at base. P. franciscoi is morphologically related to P. candida and P. sclerophylla although these two species are not reported for Colombia. A taxonomic key to the section in Colombia is included. The distribution, ecology and conservation status of the new species are also considered in this paper.